Design and Implementation of an IoT-Based Solar Power Measurement System for Charging Stations of Electric Vehicles - Ko, Mg Myo Ko; Mon, Ei; Htike, Than Than; Tun, Hla Myo (The Indonesian Institute of Science and Technology Research, 2025)
Because of its potential to improve monitoring and management skills, integrating Internet of Things (IoT) technology with renewable energy systems has attracted much interest recently. This study describes an experiment that uses an IoT-based solar power monitoring system to measure the output power of a solar panel in real-time. A 50-watt solar panel is used in this paper to demonstrate the design and execution of an Internet of Things-based solar power monitoring system. The use of the IoT can significantly improve solar energy surveillance by better monitoring solar panel performance. The system comprises a 50-watt solar panel, a microcontroller unit, various sensors for measuring power, voltage, current, and temperature, and a wireless communication module for transmitting data. The collected data is sent to a cloud-based platform, where it is processed and analyzed. The results indicate that the Internet of Things (IoT)- based solar power measuring system provides a scalable solution for broader applications in renewable energy management and improves the reliability and precision of power-producing data. Real-time solar power generation monitoring is the goal of the proposed system, which would allow for effective energy management and optimization.